Validation of an innovative analytical method for simultaneous quantification of alpha-cyano-4-hydroxycinnamic acid and the monoclonal antibody cetuximab using HPLC from PLGA-based nanoparticles - Ferreira, Natália N. [UNESP]; Boni, Fernanda I. [UNESP]; Baltazar, Fátima; Gremião, Maria P.D. [UNESP] (Elsevier, 2020)
Accumulating evidence has been suggesting that combining two or more anticancer drugs can provide additive or synergistic effects, improving therapeutic efficacy and delaying resistance. Nowadays, advances in nanotechnology-based delivery systems have enabled the association of different drugs into a single carrier and provided therapeutic gains to the proposed regimen. However, a new strategy also requires innovative analytical approaches that assess loading capacity, biological performance, and also comprehend the mechanisms of action. Alpha-cyano-4-hydroxycinnamic acid (CHC) and the monoclonal antibody (mAb) cetuximab (CTX) are explored worldwide for their therapeutic benefits against multiple cancer cells. The present work aims to develop and validate a new method for simultaneous quantification of CHC and CTX in nanoparticulate systems by using reverse phase high-performance liquid chromatography (RP-HPLC) with ultraviolet (UV) detection for CHC, and fluorescence detection for CTX. This method was designed following the guidelines of the International Conference on Harmonization ICH Q2 (R1) and the Food and Drug Administration (FDA) - Guidance for Bioanalytical Method Validation. Chromatographic separation was performed on a C18 column with the mobile phase composed by water, 0.1 % (v/v) trifluoroacetic acid (TFA) and acetonitrile (ACN)-0.1 % TFA on gradient mode at a flow rate of 0.6 mL/min. The performance of the present method was evaluated by system suitability; therefore, linearity, accuracy, precision, detection, limit of detection / limit of quantification, and robustness were also highlighted. Specificity was demonstrated by the chromatographic analyses of CHC and CTX, subjected to several informative stress conditions. The developed method was also successfully used for the first time to quantify the CHC and CTX content in poly(lactic-co-glycolic acid)-based nanoparticles. In conclusion, this new and rapid method presented acceptable analytical performance and can be helpful to simultaneously quantify CHC and CTX in future studies applied to anticancer therapy.
Keywords: Alpha-cyano-4-hydroxycinnamic acid; Cetuximab; Experimental anticancer drug; Method validation; Poly(lactic-co-glycolic acid)-based nanoparticles; Reversed phase HPLC